METHOD FOR FMD VIRUS 146S COMPONENT CONCENTRATION DETERMINATION WITH REAL-TIME REVERSE TRANSCRIPTION – POLYMERASE CHAIN REACTION IN VACCINE RAW MATERIALS - M. I. Doronin; A. M. Timina; D. A. Lozovoy; V. A. Starikov; D. V. Mikhalishin; N. N. Medvedeva; А. V. Borisov (Ветеринария сегодня)
Method for determination of foot-and-mouth disease (FMD) virus 146S component concentration with real-time reverse transcription – polymerase chain reaction (rtRT-PCR) in vaccine raw materials is developed. Negative regression model of  С146S = (30.269 – Ct)/4.155 type allowing determination of FMDV 146S particle concentrations based on the amplification threshold cycle values (Ct) is proposed. It has been experimentally proven that the quantity of the 146S component determined by the real-time RT-PCR method using developed regression model and contained in the inoculation dose of FMD vaccine confers protection to the vaccinated animals against generalized FMD of A, O, Asia-1 types. rtRT-PCR method is highly sensitive and allows rapid and highly reliable estimation of  the 146S antigen concentration in FMD vaccine. The method for 146S particle quantity determination by real-time RT-PCR using the regression model is reliable and demonstrates high correlation (95.5–99.0%) with the complement fixation test results.